Supplementation with Chinese herbal preparations protect the gut-liver axis of Hu sheep, promotes gut-liver circulation, regulates intestinal flora and immunity - Liu, Zilong; Wang, Huihui; Ma, Keyan; Li, Qiao; Wu, Yi; Qi, Xingcai; Song, Juanjuan; Wang, Chunhui; Ma, Youji; Li, Taotao (Frontiers in Immunology, 2024)
The gut-liver axis in ruminants can explain nutrient regulation, the gut-liver cycle, and immune function in ruminant biology through the gut microbe-gut metabolite-liver metabolite relationship. to investigate the effects of herbal feed additives on the gut-liver axis of Hu sheep. In this study, a broadly targeted UPLC-MS/MS metabolomics approach and 16s sequencing of gut microorganisms were used to detect, identify and quantify changes in ileal microorganisms, liver metabolites and ileal metabolites following the addition of Chinese herbal preparations. The addition of a 0.5% herbal feed additive increased ileal IgA, IgG and complement C3 levels. The addition of Chinese herbal preparations can increase the abundance of Firmicutes, Actinobacteriota, Bacteroidota, at the portal level of the ileum, increase the metabolism of organic matter and its derivatives, bile acids, amino acids and their metabolites, coenzymes, and vitamins in the liver and ileum, enhance nutrient absorption and waste metabolism, accelerate liver metabolism, promote gut-liver circulation, and improve ileal and liver immunity. This study provides a theoretical basis for understanding the effects of herbal feed additives on the gut-liver axis in ruminants.